1999
DOI: 10.1097/00000658-199909000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Hospital Volume Can Serve as a Surrogate for Surgeon Volume for Achieving Excellent Outcomes in Colorectal Resection

Abstract: ObjectiveTo examine the association of surgeon and hospital case volumes with the short-term outcomes of in-hospital death, total hospital charges, and length of stay for resection of colorectal carcinoma. MethodsThe study design was a cross-sectional analysis of all adult patients who underwent resection for colorectal cancer using Maryland state discharge data from 1992 to 1996. Cases were divided into three groups based on annual surgeon case volume-low (Յ5), medium (5 to 10), and high (Ͼ10)-and hospital vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
231
4
13

Year Published

2002
2002
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 367 publications
(262 citation statements)
references
References 33 publications
14
231
4
13
Order By: Relevance
“…[20][21][22] In addition, for colorectal cancer, it has been demonstrated that the number of assessed lymph nodes increases as surgical and hospital volumes increase. [22][23][24][25][26] The exact contribution of each of these factors to the improvement in survival with increasing TLN or whether TLN is a surrogate of overall quality as it pertains to postoperative care, follow-up, or subsequent therapy could not be determined in the current study. Irrespective of the reasons for these differences, patients with more TLNs assessed have improved survival, and this finding has important implications for clinical prognostication.…”
Section: Lymph Nodes In Small Bowel Carcinoma/overman Et Almentioning
confidence: 99%
“…[20][21][22] In addition, for colorectal cancer, it has been demonstrated that the number of assessed lymph nodes increases as surgical and hospital volumes increase. [22][23][24][25][26] The exact contribution of each of these factors to the improvement in survival with increasing TLN or whether TLN is a surrogate of overall quality as it pertains to postoperative care, follow-up, or subsequent therapy could not be determined in the current study. Irrespective of the reasons for these differences, patients with more TLNs assessed have improved survival, and this finding has important implications for clinical prognostication.…”
Section: Lymph Nodes In Small Bowel Carcinoma/overman Et Almentioning
confidence: 99%
“…For example, Harmon et al examined the association of surgeon and hospital case volumes with the outcome of patients with colorectal cancer. They showed that "medium-volume" surgeons achieved excellent outcomes similar to "high-volume" surgeons when operating in "medium-volume" or "highvolume" hospitals, while the results of "low-volume" surgeons improved with increasing hospital volume but never reached those of the "high-volume" surgeons [6]. In contrast, Marusch et al [7] failed to show significant associations between hospital caseload and postoperative outcome in 2,293 colorectal cancer patients undergoing surgery.…”
Section: Introductionmentioning
confidence: 99%
“…[16;17] However, studies on mortality among patients with colon cancer showed conflicting results: some demonstrated an association between mortality and hospital volume or teaching status, while others did not. [18][19][20][21][22][23][24] Aim of this study was to describe variation in staging, treatment patterns and outcome according to region and, according to type and volume of individual hospitals among patients with colon cancer in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%